b - Abascal, Julio; Barbosa, Simone; Fetter, Mirko; Gross, Tom.; Palanque, Philippe; Winckler, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The four-volume set LNCS 9296-9299 constitutes the refereed proceedings of the 15th IFIP TC13 International Conference on Human-Computer Interaction, INTERACT 2015, held in Bamberg, Germany, in September 2015. The 41 papers included in the first volume are organized in topical sections on accessibility; accessible interfaces for blind people; accessible interfaces for older adults; affective HCI and emotions and motivational aspects; alternative input; alternative input devices for people with disabilities; interfaces for cognitive support; brain-computer interaction; cognitive factors.
Accessibility -- Accessible interfaces for blind People -- Accessible interfaces for older adults -- Affective HCI and emotions and motivational aspects -- Alternative Input -- Alternative input devices for people with disabilities -- Interfaces for cognitive Support -- Brain-computer interaction -- Cognitive factors.
Keywords: Computer science; Artificial intelligence; Education; Software engineering; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Artificial Intelligence; Computers and Society; Computers and Education; Software Engineering